Free radicals scavenging activity and antimicrobial potential of leaf and fruit extracts of Sapindus mukorossi Gaertn. against clinical pathogen - Reetika Singh; Nishi Kumari; Gopal Nath (International Journal of Phytomedicine, 2016)
Antioxidant activity of fruit and leaf extracts of Sapindus mukorossi Gaertn. was evaluated through β- carotene/linoleic acid bleaching assay and hydrogen peroxide scavenging activity. Antimicrobial potential of extracts was also assessed against human disease causing pathogens. In fruit extract, highest antioxidant activity (76.64 ± 1.06) was found in aqueous extract and leaf extract showed maximum antioxidant activity (90.82 ± 1.11) in methanolic extract. In fruit, maximum H2O2 scavenging activity was found in methanolic extract and in leaf maximum H2O2 scavenging activity (10.53 ± 0.72) in ethanolic extract. Both, fruit and leaf extract have showed significant antimicrobial activity against most of the pathogens. In fruit extract, methanolic and aqueous extract showed potent antimicrobial activity against all tested organisms except Candida albicans. All extract of fruit showed maximum inhibition zone (diameter) against Candida tropicalis, methanolic extract (12.50 ± 0.29), aqueous extract (11.66 ± 0.33) and ethanolic extract (10.16 ± 0.16). In leaf extract, maximum inhibition zone (9.66 ± 0.52) was formed by ethanolic extract against Salmonella Typhimurium. Fruit and leaf extracts have shown more activity against Gram negative bacteria.